Bibliometric analysis of research trends in Chinese cultural and creative industries - Qi, Yujie (Frontiers in Communication, 2025)
Over the past two decades, research on cultural and creative industries (CCIs) has grown significantly, with China emerging as a focal area. This study employs a bibliometric analysis of Scopus data to map research trends in Chinese CCIs, examining co-authorship, co-occurrence, citation, bibliographic coupling, and co-citation patterns. The findings highlight the dominance of Western contributions and influential authors, as well as strong thematic and citation interactions. However, limited collaboration among authors presents opportunities for future partnerships, offering insights into the evolving dynamics of Chinese CCIs research.